A Complex In Vitro Degradation Study on Polydioxanone Biliary Stents during a Clinically Relevant Period with the Focus on Raman Spectroscopy Validation - Loskot, Jan; Jezbera, Daniel; Zmrhalová, Zuzana Olmrová; Nalezinková, Martina; Alferi, Dino; Lelkes, Krisztina; Voda, Petr; Andrýs, Rudolf; Fučíková, Alena Myslivcová; Hosszú, Tomáš; Bezrouk, Aleš (Polymers, 2022)
Biodegradable biliary stents are promising treatments for biliary benign stenoses. One of the materials considered for their production is polydioxanone (PPDX), which could exhibit a suitable degradation time for use in biodegradable stents. Proper material degradation characteristics, such as sufficient stiffness and disintegration resistance maintained for a clinically relevant period, are necessary to ensure stent safety and efficacy. The hydrolytic degradation of commercially available polydioxanone biliary stents (ELLA-CS, Hradec Králové, Czech Republic) in phosphate-buffered saline (PBS) was studied. During 9 weeks of degradation, structural, physical, and surface changes were monitored using Raman spectroscopy, differential scanning calorimetry, scanning electron microscopy, and tensile and torsion tests. It was found that the changes in mechanical properties are related to the increase in the ratio of amorphous to crystalline phase, the so-called amorphicity. Monitoring the amorphicity using Raman spectroscopy has proven to be an appropriate method to assess polydioxanone biliary stent degradation. At the 1732 cm-1 Raman peak, the normalized shoulder area is less than 9 cm-1 which indicates stent disintegration. The stent disintegration started after 9 weeks of degradation in PBS, which agrees with previous in vitro studies on polydioxanone materials as well as with in vivo studies on polydioxanone biliary stents.
Keywords: Young’s modulus; tensile strength; biliary stent; Raman spectroscopy; degradation; polydioxanone; differential scanning calorimetry